(untitled) (Research, Society and Development, 2022)
In view of the Covid-19 pandemic, it is necessary to know the emotional and behavioral issues faced by children during the period of social withdrawal. The present study aimed to identify the psychological and emotional needs of preschool children, aged 4 to 6 years, from two private schools in a city in Vale do Caí/RS. Six parents participated, aged between 30 and 43 years, all of them had completed high school and were married. This is a qualitative study, with multiple case study design. The interviews were conducted through Google.Meet, the data were recorded and transcribed, submitted to Bardin’s qualitative content analysis and NVIVO QSR software. The results were organized into categories about the perception of parents regarding the children’s psychological and emotional needs, as well as coping strategies developed by the children’s parents and the experiences lived in this context. The importance of the face-to-face educational institution for the healthy development of preschoolers was highlighted, according to their parents’ reports. Learning and the school context have an impact on children’s mental health, and it is important that family and school work together for the best development of the child.